Analysis of Customer Satisfaction in The Online Shopping System for Fashion Product - Rini Gusnita (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2021)
Consumer interest in online shopping will be very high if they are satisfied with the products offered by online stores. The satisfying experience that is felt when buying a certain product will support consumers to buy again. Therefore, the research objectives to be achieved in this study are to determine the factors that affect customer satisfaction in the online shopping system for fashion products, to know the most dominant factors affecting consumer satisfaction in the online shopping system for fashion products and to know the lowest factors. which affects customer satisfaction in the online shopping system for fashion products. In this study, the study population is all consumers who have experience doing an online shopping system for fashion products in Bengkalis. The method of data collection is carried out by researchers by means of a survey through a questionnaire instrument. The research questionnaire was presented to respondents through the distribution of questionnaires online in an internet link uploaded by researchers The total number of samples obtained was 100 respondents overall. The sampling technique used is a non-probability sampling technique with the type of snowball sampling. The results obtained indicate that the cost aspect is the most dominant factor affecting customer satisfaction while product quality is the lowest or less dominant factor affecting customer satisfaction, where both factors are included in the high category. This research basically has several limitations, namely the difficulty in distributing questionnaires during the COVID-19 pandemic in the City of Bengkalis, so researchers have to distribute questionnaires through social media and the limited sources of information used as reference material. It is hoped that in the future this research can continue to be developed further according to the times.